2014
DOI: 10.1177/1071100714550650
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Readability of Online Foot and Ankle Patient Education Materials

Abstract: This study provides authors of patient education materials with simple editing techniques that will allow for the improvement in the readability of online patient educational materials. The improvement in readability will provide patients with more comprehendible education materials that can strengthen patient awareness of medical problems and treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 15 publications
1
64
0
Order By: Relevance
“…The guidelines advise simple interventions to improve readability including limiting sentences to 10 words, replacing complex medical terminology with the definition, and limiting the use of medical jargon 37 . Previous literature has demonstrated that the application of these interventions can both improve readability and patient knowledge without sacrificing medical content 38 . For example, POPDI‐6 uses the phrase “lower abdominal pressure”; this is a vague term that can be communicated more clearly by providing a medical analogy or simplifying terminology.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines advise simple interventions to improve readability including limiting sentences to 10 words, replacing complex medical terminology with the definition, and limiting the use of medical jargon 37 . Previous literature has demonstrated that the application of these interventions can both improve readability and patient knowledge without sacrificing medical content 38 . For example, POPDI‐6 uses the phrase “lower abdominal pressure”; this is a vague term that can be communicated more clearly by providing a medical analogy or simplifying terminology.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that despite complex medical content, the readability of PEMs can be significantly improved by using simpler sentences and shorter words. Dalziel et al [12] reported on an average grade level improvement of 3.1 in PEM comprehension by simple substitution of multisyllabic words, with a further reduction by simplification of sentence structure [25,26]. These simple measures are easily applicable to German PEMs and might help to improve their readability significantly.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that additional reductions in grade level readability would be possible by further alterations to sentence structure and this is supported by the existing literature. 15,16 Horner et al developed a framework for revision of PIMs based on targeting specific obstructions to comprehension. 15 Their framework provided a four-step process to improve upon existing PIMs.…”
Section: Readability Of Patient Information Materialsmentioning
confidence: 99%